2023
DOI: 10.1101/2023.07.04.546637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An ancient split of germline and somatic stem cell lineages in Hydra

Abstract: In many animals, germ cell segregation occurs during early embryogenesis to protect the genome, but its origin in basal metazoans is controversial. Here, we show in the freshwater polyp Hydra by clonal analysis and transgenic animals that interstitial stem cells comprise two separate stem cell populations, i.e., germline and multipotent somatic stem cells. We isolated genetically labelled stem cells for a global transcriptome study and discovered a broad set of germline-specific/enriched genes including Prdm9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…The same applies to the change from female to male. In Hydra , molecular markers for female GSCs and male GSCs have been identified (28, 29). In our previous study, we have identified GCS-like cells in gonads of F. ancora (30).…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to the change from female to male. In Hydra , molecular markers for female GSCs and male GSCs have been identified (28, 29). In our previous study, we have identified GCS-like cells in gonads of F. ancora (30).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrozoan i-cells constitute a pool of pluri-or multipotent stem cells that contributes to somatic cells and the germline (Bosch & David, 1987;Holstein, 2023;Houliston et al, 2010;Muller et al, 2004;Varley et al, 2023). In Hydra, Northern hybridization of smad1/5 indicated that it is upregulated in i-cells (Hobmayer et al, 2001), while transcriptomic analysis showed the upregulation of the BMP receptor actr1 in multipotent interstitial cells and smad1/5 and BMP antagonist dand in germline stem cells (Nishimiya-Fujisawa et al, 2023). In Hydractinia, the expression a putative bmp receptor has been detected in developing oocytes and the male gonophore gastrodermis (Sanders et al, 2014).…”
Section: Potential Role Of Bmp Signaling In the Reproductive Regionmentioning
confidence: 99%